Service Recovery in Collaborative Consumption Settings - Shuqair, Saleh (2019)
Shuqair, S., & Pinto, D. C. (2019). Service Recovery in Collaborative Consumption Settings. In Proceedings of the European Marketing Academy, 48th (pp. 1-11). European Marketing Academy (EMAC). http://proceedings.emac-online.org/pdfs/A2019-4355.pdf